Transnational crime: European and Chinese perspectives - Billis, Emmanouil (The Queen Mary-Remin series on comparative criminal justice issues, 2019)
Introduction / Valsamis Mitsilegas, Saskia Hufnagel and Anton Moiseienko -- The global governance of transnational crime : implications for justice and the rule of law / Valsamis Mitsilegas -- Introduction to anti-money laundering regulations in China : institutions, legal framework and practices / Shi Yanan -- Acts of charity and acts of terrorism : regulation and prosecution / Clive Walker -- On the improvement of criminal legislation and criminal policy to deter cross-border money laundering in China / Wang Wenhua -- Transnational cybercrime and cybercrime by transnational organisations / Petter Gottschalk -- Paint it black : "simple" and increasingly "professional" looting of antiquities with metal detectors in East Asia / Samuel Hardy -- From canvas to ashes : understanding the implications of the Westfries Museum and Kunsthal thefts for the Dutch art world / Naomi Oosterman -- Expression crimes and the creation and protection of historical memory by means of criminal law / Emmanouil Billis -- Relocating bribery : facilitation payments as a crime against the market / Simon Bronitt -- Credit card fraud in Chinese criminal law / Liu Mingxiang -- China's legal framework and challenges of the freezing, seizure and confiscation of financial crime proceeds / Cheng Lei -- Targeting transnational environmental crime through a multifaceted approach: towards an inclusive governance of serious threats to sustainable development / Grazia Maria Vagliasindi -- Preventing illicit waste-exports from the Netherlands to China / Toine Spapens, Shanna Mehlbaum and Rudie Neve -- Motivators for IUU fishing in the Indo-Pacific / Erika J Techera and Jade Lindley